TINJAUAN YURIDIS TERHADAP PENYALAH GUNA NARKOTIKA MELALUI PENDEKATAN PENCEGAHAN DENGAN REHABILITASI YANG TERINTEGRASI - M Sadam Husin; Mukhlis R; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Addiction or addiction to Narcotics drugs causes havoc for people who use or abusers and is a threat to the life of the abuser itself be it family, national security, nation and state. In Law Number 35 Year 2009 concerning Narcotics, it is explained that Narcotics abusers are not required to be imprisoned but to be punished with Rehabilitation because the Narcotics Law guarantees the abuser to get Rehabilitation efforts (Article 4d). In this paper the author focuses on Narcotics Abusers who In practice, the view of Narcotics Defenders as criminals is still more dominant than the health and healing approaches to Narcotics addiction. The purpose of writing this thesis: first, to find out how to implement the Integrated Prevention Approach in Rehabilitating Narcotics Abusers. Second, to find out what are the obstacles to implementing the Integrated Prevention Approach in Rehabilitating Narcotics Abusers. Third, to find out what are the efforts to overcome the obstacles in implementing the Integrated Prevention Approach in Rehabilitating Narcotics Abusers.The author conducts research using the normative juridical method or literature study in order to obtain secondary data through documentary studies, namely by studying and analyzing comparatively descriptive of the laws and regulations with theories that have a relationship to the problems studied. From the research results, there are three main things that can be concluded: First, Prevention of Narcotics Abuse with Integrated Rehabilitation is understanding the meaning of Rehabilitation as a whole. Second, Constraints in the implementation of Integrated Rehabilitation can be seen from the perspective of law enforcement officers, the Integrated Assessment Team (TAT) and seen from the Narcotics Abuse Victims themselves. Third, efforts that can be made in facing obstacles in the implementation of Integrated Rehabilitation which are seen from the perspective of law enforcement officials, the Integrated Assessment Team (TAT) and Victims of Narcotics Abuse.Keywords: Rehabilitation - Abuse - Narcotics -Integrated